2008
DOI: 10.1007/s10142-008-0081-z
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrin gene expression provides an indicator of low temperature and drought stress: transcriptome-based analysis of Barley (Hordeum vulgare L.)

Abstract: Low temperature and drought have major influences on plant growth and productivity. To identify barley genes involved in responses to these stresses and to specifically test the hypothesis that the dehydrin (Dhn) multigene family can serve as an indicator of the entire transcriptome response, we investigated the response of barley cv. Morex to: (1) gradual drought over 21 days and (2) low temperature including chilling, freeze-thaw cycles, and deacclimation over 33 days. We found 4,153 genes that responded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 65 publications
7
98
0
2
Order By: Relevance
“…Drought stress (DS) and low temperature stress (LTS) are among the important environmental factors that limit plant growth and productivity (Tommasini et al, 2008). Seedling establishment is a critical process to plant growth, especially under adverse environmental conditions (Bohnert et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress (DS) and low temperature stress (LTS) are among the important environmental factors that limit plant growth and productivity (Tommasini et al, 2008). Seedling establishment is a critical process to plant growth, especially under adverse environmental conditions (Bohnert et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…DHNs are encoded by a dispersed multigene family and are differentially regulated, at least in higher plants. For example, 13 Dhn genes have been identified in barley (Hordeum vulgare), dispersed over seven genetic map locations (Choi et al, 1999;Svensson et al, 2002) and regulated variably by drought, low temperature, and embryo development (Tommasini et al, 2008). DHNs are localized in various subcellular compartments, including cytosol (Roberts et al, 1993), nucleus (Houde et al, 1995), chloroplast (Artus et al, 1996), vacuole (Heyen et al, 2002), and proximal to the plasma membrane and protein bodies (Asghar et al, 1994;Egerton-Warburton et al, 1997;Puhakainen et al, 2004).…”
mentioning
confidence: 99%
“…It seems that accumulation of dehydrins is a common feature of cold acclimation and onset of dormancy, and levels of dehydrin transcripts stay very high during the winter (Wisniewski et al 1996;Yakovlev et al 2008). Many studies report a positive correlation between the accumulation of dehydrin transcripts or proteins and tolerance to freezing, drought, or salinity (Karlson et al 2003;Kosová et al 2007;Mehta et al 2009;Rampino et al 2006;Rorat et al 2006;Tommasini et al 2008;Wisniewski et al 2008;Hara 2010). Joosen et al (2006) have demonstrated a positive correlation between cold acclimation and upregulation of K 2 type dehydrins.…”
Section: Discussionmentioning
confidence: 99%